Gallipoli : untold stories from war correspondent Charles Bean and front-line Anzacs - King, Jonathan, 1942-; Bowers, Michael, 1961-; Bean, C. E. W. (Charles Edwin Woodrow), 1879-1968; Schuler, Phillip F. E. (North Sydney, N.S.W. : Random House Australia, 2008)
" To commemorate the 90th anniversary of the Anzac landing, Gallipoli : untold stories ... tells the real story through the private diaries and newspaper reports of Charles Bean, Australia's official war correspondent and Sydney Morning Herald journalist. Bean's misgivings about the campaign are reinforced by graphic and rarely seen photographs taken by Age photographer Phillip Schuler. There are also stories from the front line, collected in a seach for letters, diaries and memorabilia from the families of Australian and New Zealand soldiers who served on Gallipoli."-- Provided by publisher.
At head of title on cover : The Sydney Moring Herald, The Melbourne Age.
Previous ed. published as: Gallipoli : untold stories from war correspondent Charles Bean and front-line Anzacs : a 90th anniversary tribute. Transworld, 2005.
Includes bibliographical references and index.
Keywords: World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula -- Personal narratives, Australian